2002
DOI: 10.1006/viro.2001.1274
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Human Cytomegalovirus Glycoprotein O (gO) in Cell Fusion and a New Hypervariable Locus

Abstract: A cell fusion assay using fusion-from-without (FFWO) recombinant adenoviruses (RAds) and specific antibody showed a role in fusion modulation for glycoprotein gO, the recently identified third component of the gH/gL gCIII complex of human cytomegalovirus (HCMV). As in HCMV, RAd gO expressed multiple glycosylated species with a mature product of 125 kDa. Coexpression with gH/gL RAds showed gCIII reconstitution in the absence of other HCMV products and stabilisation by intermolecular disulfide bonds. Properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
60
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 70 publications
6
60
0
Order By: Relevance
“…Given that the role of gH/gL in entry is highly conserved among the herpesviruses, it seemed likely that gH/gL/gO might be involved in entry into fibroblasts. Consistent with this notion, Paterson et al showed that anti-gO antibodies decreased fusion from without caused by infection of cells with HCMV AD169 (37). These observations supported our working model in which gH/gL/UL128-131 mediates entry into epithelial and endothelial cells, while gH/gL/gO mediates entry into fibroblasts.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Given that the role of gH/gL in entry is highly conserved among the herpesviruses, it seemed likely that gH/gL/gO might be involved in entry into fibroblasts. Consistent with this notion, Paterson et al showed that anti-gO antibodies decreased fusion from without caused by infection of cells with HCMV AD169 (37). These observations supported our working model in which gH/gL/UL128-131 mediates entry into epithelial and endothelial cells, while gH/gL/gO mediates entry into fibroblasts.…”
supporting
confidence: 73%
“…It is also reasonable to suggest that fibroblast adaptation includes changes in gO. The gO genes (UL74) of several laboratory and clinical strains and clinical isolates are highly variable (up to 25% of amino acids) (10,35,37,47). However, it is important to note that AD169-derived UL131-repair virus can infect epithelial and endothelial cells (52).…”
mentioning
confidence: 99%
“…For gH/ gL, two alternative complexes have been described: a complex of gH (UL75), gL (UL115), and gO (UL74) (16,24) and a complex of gH, gL, and pUL128, pUL130, and pUL131A (1,56). HCMV gH/gL complexes are supposed to play a role in promoting fusion of the viral envelope and cellular membranes and probably act in concert with gB and potentially through binding to integrin receptors (11,22,36,37,52,58). Recently, the role of the gH/gL/gO complex was analyzed in more detail.…”
mentioning
confidence: 99%
“…gO is N and O glycosylated and contains an amino-terminal hydrophobic membrane anchor which is cleaved off during processing (17,49,50). Data on the contribution of gO to the fusogenic activity of the gH/gL complex are controversial (36,52). It is also not exactly known whether gH/gL/gO complexes are consistently incorporated into HCMV particles or whether gO merely acts as a chaperone to promote incorporation of gH/gL complexes into virions (44,60).…”
mentioning
confidence: 99%
“…Data about the functional role of the main gB types in HCMV pathogenesis and their relationship with the clinical outcome of HCMV disease and virus cell/tissue tropism are controversial and in some cases, contradictory (4,8,10). The components of the glycoprotein envelope complex, gH, gL and gO, encoded by the ORFs UL75, UL115 and UL74, respectively, have also been shown to be polymorphic (5,20,25).…”
mentioning
confidence: 99%